Perbandingan Reaksi Pasar atas Seasoned Equity Offering dengan Tujuan Investasi dan Membayar Utang - Bella Sri Lestari, Ni Komang; Wirama, Dewa Gede (E-Jurnal Akuntansi, 2020)
This research compares market reaction to seasoned equity offering (SEO) with investment purpose and debt repayment purpose. The research was triggered by pecking order theory’s. The sample of this research is 62 Indonesian public companies that carried out SEO during the 2013 to 2019 period. The SEO announcement date is used as event date. The event window is five days around the event date. Abnormal return is measured by market-adjusted model. The result of independent sample t-test shows that market reaction to SEO with investment purpose is better than market reaction to SEO with debt repayment purpose. Average cumulative abnormal return (CAR) of SEO with investment purpose is 0.038 and for SEO with debt repayment purpose is minus 0.006. The difference is statistically significant (p-value=0.011). Therefore, it is concluded that  markets response to additional equity offering, in this case using SEO, depends on the purpose of the SEO . Keywords: Seasoned Equity Offering; Market Reaction; Abnormal Return; Market-Adjusted Model.